Electrochemical mineralization of direct blue 71 with boron-doped diamond anodes: Factor analysis and mechanisms study. Issue 1 (February 2022) - Xu, Jiangyan; Sun, Minjia; Zhang, Chunyong; Wu, Meisheng; Fu, Degang
Abstract: Electrochemical oxidation with boron-doped diamond (BDD) had been well established as an outstanding technology for wastewater treatment. In this study, BDD technology was initially used to degrade direct blue 71 (DB71) dye under galvanostatic conditions. The main and joint effects of three operating parameters (supporting electrolyte concentration, applied current density and flow rate) on oxidation performance were estimated by Box-Behnken design. Among the variables, sulfate concentration displayed the most unique roles in DB71 degradation. The optimum operating conditions obtained by response surface methodology were: 2.0 mM Na2 SO4, applied current density of 7.75 mM cm −2 and flow rate of 600 mL min −1, which gave a decolorization percentage of 100%, a mineralization percentage of 50.2%, as well as an energy consumption of 3845 kWh kg −1 TOC and a mineralization efficiency of 8.7% at 120 min of electrolysis. In addition, based on the quantum chemistry calculation and identified reaction intermediates detected by LC/MS analysis, a plausible degradation sequence of DB71 in BDD anode cells was also proposed. The results obtained were expected to offer useful guidance for the application of BDD technology as powerful and green option for treating DB71 pollutants. Graphical Abstract: ga1 Highlights: Direct blue 71 could be effectively oxidized with boron-doped diamond. The electrolytic degradation of DB71 was optimized by Box-Behnken design. Sulfate electrolytes displayed significant and unique roles in DB71 degradation. DFT, FOA and LC/MS analyses were all employed for mechanistic study. A detailed oxidation pathway of DB71 on BDD anodes was proposed and discussed.